Stability investigation of water based exfoliated graphene nanofluids - Arifutzzaman, A.; Ismail, Ahmad Faris; Yaacob, Iskandar Idris; Alam, Md Zahangir; Khan, Ahsan Ali (IOP Publishing Ltd, 2019)
Until now stability is a crucial technical challenge to prepare a homogeneous dispersion. The main purpose of this work is to experimentally investigate the suspension stability of the exfoliated Graphene (Gr) suspension in deionized water (DW) (Gr/DW). Five different samples were prepared by varying the exfoliated Gr volume fraction from 0.11 to 0.30 % in deionized water. For the observation of sedimentation photo capturing was used as a primary technique. Finally stability of the exfoliated Gr/DW nanofluids were monitored quantitatively with the aid of optical absorbance measurements using ultra violet-visible absorbance spectroscopy. The wavelength range of light was varied from 200 to 800 nm. Digital photographs of Gr/DW nanofluid samples after preparation of about 25 days shown homogeneous and visibly there was no sedimentation in the suspensions. The peak absorbance of Gr/DW nanofluids was appeared at the wavelength of 280 nm. For a certain volume fraction, absorbance was decreased monotonically with the increasing wavelength. The relative concentration of the Gr/DW samples was decreased due to slight agglomeration by the increasing concentration of precipitation with time. After 600 hours (~25 days), the lowest and maximum precipitation rate were appeared ~ 6 and ~ 10 % for the Gr/DW samples with the volume fraction of 0.11 and 0.30 % respectively. Different amount of exfoliated Gr loading affect the rate of sedimentations of exfoliated Gr/DW nanofluids.